Strategi Komunikasi Pemasaran Digital My Nasha Hotel Tigaras dalam Meningkatkan Pengunjung - Naibaho, Nadiva Auralia; Ritonga, Muhammad Husni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study deals with effective marketing communication strategies in a digital context at My Nasha Hotel Tigaras. As a business in the service industry, My Nasha Hotel must have a strong marketing communication plan to cope with the increasingly stringent competition in the digital realm. The company's efforts to reach the target market with value and message, identify the target audience, and use digital media relevant to the target is known as its marketing communication strategy. The aim of this research is to identify strategies to increase room occupation, expand the range of promotions, and build the corporate image. This research method uses a qualitative approach to data collection techniques through observations, interviews, and documentation. The research tools used include researchers themselves, interview guides, and field records. The results of research on the digital marketing communication strategy of My Nasha Hotel Tigaras to increase visitors show that the hotel has implemented 4P (Product, Price, Place, Promotion) in digital marketing communications. In addition, collaborations with offline and online travel agents, as well as government agencies, are also part of the strategy to increase visitors' interest.